Aviation business growth; Does ground movement capacity and air space capacity matter? - Muthoni, Gloria Beth; Patel, Pratiksha (American Journal of Social Sciences and Humanities, 2024)
Growth in any firm’s business is critical as a long-term objective of such a firm. The study thus focused on the influence of ground movement capacity and air space capacity on the growth of aviation businesses at Wilson Airport. The guiding objectives of this study were: to establish the effect of ground movement capacity on aviation business growth in Kenya and to assess the effects of airspace capacity on in Kenya. The study was guided by theory of constraints. The study employed an explanatory research design. The study targeted 117 respondents based at Wilson Airport. A Census survey was used in this study to collect information from all participants in the population. The study collected primary data using questionnaires. In testing for reliability, Cronbach’s alpha coefficient was applied. The Statistical Package for the Social Sciences (SPSS) was used for data analysis. Inferential data were analyzed using correlation and multiple regressions. The study findings revealed that ground movement capacity has a positive and significant effect on aviation business and airspace capacity has a positive and significant effect on aviation business growth. Ground movement capacity was an important determinant of aviation business growth. Kenya Civil Aviation Authority and Kenya Airports Authority should pool resources and increase the ground movement equipment and facilities. The study recommends that future researcher’s study on the influence of public, private partnership to increase the ground movement capacity on aviation growth can also be conducted.